The effect of L-carnitine in reactive oxygen species reduction and apoptotic gene expression in mice after cyclophosphamide: An experimental study - Majid Almasi; Golnaz Shafiei; Hossein Nikzad; Mohammad Karimian; Ghazaleh Moshkdanian (International Journal of Reproductive BioMedicine)
Background: Cyclophosphamide (CP), a utilized anticancer drug, is known to cause infertility in women. However, L-carnitine (LC), an antioxidant, has been shown to offer protective benefits against infertility. Objective: This study aimed to evaluate the levels of reactive oxygen species (ROS) and apoptotic gene expression in mice treated with CP and LC. Materials and Methods: 24 NMRI female mice (6–8 wk, 30 ± 5 gr) were divided into 4 groups: control group: received normal saline intraperitoneal (IP) injection for 10 days; CP group: received 75 mg/kg of CP as a single IP on the 10 th day of the experiment; LC group: received 200 mg/kg of LC IP for 10 days; LC+CP group: received LC for 10 days and CP single IP injection on the 10 th day of the experiment. After 10 days, mice were superovulated. The oviducts were then removed, and the oocytes of each group were collected for evaluating apoptotic gene expression B-cell lymphoma 2(Bcl2), Bcl2-associated X(Bax), and Caspase3 via real-time polymerase chain reaction and intracellular ROS levels by dichloro-dihydro-fluorescein diacetate fluorescence staining. Results: Data revealed that LC in the LC+CP group significantly increased Bcl2 gene expression (p = 0.01), and decreased Bax and Caspase3 gene expression compared to the CP group (p = 0.03, p = 0.04). LC decreased the ROS level in the LC+CP group compared to the CP group (p < 0.001). Conclusion: Findings suggest that LC can scavenge the ROS caused by CP and modulate the apoptotic pathway via downregulating the Bax and Caspase3 genes and upregulating the Bcl2 gene in oocytes of mice exposed to CP.